System justification theory and sexual harassment in the workplace: A qualitative study of victims’ experiences in Italy - Angelo SACCO; Andrea Francesca FASANELLA; Daniela ACQUADRO MARAN; Tatiana BEGOTTI (GIornale Italiano di Psicologia e Medicina del Lavoro, 2025)
This qualitative study investigates how female employees who have experienced sexual harassment in the workplace describe system-justifying behaviors exhibited by themselves and their colleagues. The research was conducted in Italy, where recent data indicate that 13.5% of working women aged 15–70 have faced sexual harassment in their professional lives, with prevalence highest among those aged 15–24 (21.2%). A total of 25 women who self-identified as victims of workplace sexual harassment were interviewed. The questions explored the context of the harassment, the emotional responses elicited, and actions taken by both the victims and bystanders to justify or challenge the system. Findings reveal a pervasive tendency to defend and reinforce existing workplace norms to maintain organizational stability. However, this defensive attitude often perpetuates harmful behaviors, preventing the integration of new perspectives and hindering efforts to address the status quo. The study emphasizes the need for systemic and cultural changes to foster greater awareness and proactive responses to workplace sexual harassment.